2022
DOI: 10.1177/07334648221141413
|View full text |Cite
|
Sign up to set email alerts
|

Acupunch Exercise Improved Muscle Mass, Hand Grip Strength, and Sleep Quality of Institutional Older Adults with Probable Sarcopenia

Abstract: This study tested the effectiveness of a 6-month vitality acupunch (VA) exercise program on muscle mass, hand grip strength, and sleep quality in institutional older adults with probable sarcopenia. A cluster randomized controlled trial was conducted. A total of 103 older adults were assigned to the experimental group ( n = 52) and control group ( n = 51) according to the institution they inhabited. After the 6-month VA exercise intervention, the experimental group showed significant increases in muscle mass (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Furthermore, a randomized controlled trial showed that after a 6-month vitality acupunch exercise intervention, not only did the muscle strength of the participants significantly increase, but their sleep quality also improved significantly. 45 These noteworthy findings corroborated the causal relationship between traits related to sarcopenia and sleep traits identified in the reverse MR study, reaffirming the close association between sleep characteristics and sarcopenia. | 543…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Furthermore, a randomized controlled trial showed that after a 6-month vitality acupunch exercise intervention, not only did the muscle strength of the participants significantly increase, but their sleep quality also improved significantly. 45 These noteworthy findings corroborated the causal relationship between traits related to sarcopenia and sleep traits identified in the reverse MR study, reaffirming the close association between sleep characteristics and sarcopenia. | 543…”
Section: Discussionsupporting
confidence: 69%
“…Similarly, these research results strongly supported the causal relationship between symptoms related to sarcopenia, such as grip strength, walking speed, waist circumference and sleep quality, which were consistent with those of our MR study. Furthermore, a randomized controlled trial showed that after a 6‐month vitality acupunch exercise intervention, not only did the muscle strength of the participants significantly increase, but their sleep quality also improved significantly 45 . These noteworthy findings corroborated the causal relationship between traits related to sarcopenia and sleep traits identified in the reverse MR study, reaffirming the close association between sleep characteristics and sarcopenia.…”
Section: Discussionmentioning
confidence: 53%
“…Physical activity programmes can reduce cortisol levels and improve sleep quality and are an effective strategy to tackle stress and sleep complaints in adults 43. According to the meridian theory, vitality acupunch exercise can promote qi and blood circulation and has a positive effect on the sleep quality in older adults with possible sarcopenia 44. Music-based intervention appears to be a promising strategy to improve sleep quality 45.…”
Section: Discussionmentioning
confidence: 99%
“… 43 According to the meridian theory, vitality acupunch exercise can promote qi and blood circulation and has a positive effect on the sleep quality in older adults with possible sarcopenia. 44 Music-based intervention appears to be a promising strategy to improve sleep quality. 45 In addition, taking a nap is a good measure to counteract the negative consequences of insufficient sleep duration.…”
Section: Discussionmentioning
confidence: 99%
“…Jones et al[13] conducted a one-group, pre-post experimental study to examine the Healthy Beat Acupunch (non-invasive punching movements based on traditional Chinese medicine) exercise programme on sarcopenia prevention and found that it was simple, safe, appropriate, and beneficial for practice by Australian older adults with probable sarcopenia, and could improve participants’ gait speed. Another recent Taiwanese study examined the impacts of vitality acupunch exercise on older adults with possible sarcopenia, concluding that acupunch exercise has positive effects on the muscle mass, hand grip strength, and sleep quality of participants after a six-month intervention [14]. Furthermore, Pan et al [15] designed a multicomponent intervention strategy consisting of nutrition, resistance exercise, and health education for community-dwelling Chinese seniors with possible sarcopenia, which increased their muscle mass and handgrip strength and decreased the duration of the timed up-and-go test and the five-times chair stand test.…”
Section: Introductionmentioning
confidence: 99%